2016
DOI: 10.1001/jamapsychiatry.2016.0144
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA Methylation Differences With Schizophrenia in an Epigenome-Wide Association Study

Abstract: This analysis identified 172 replicated new associations with SZ after careful correction for cell type heterogeneity and other potential confounders. The overlap with previous genome-wide association study data can provide potential insights into the functional relevance of genetic signals for SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 70 publications
11
124
0
2
Order By: Relevance
“…Similar studies with remarkable findings in the investigation of a variety of diseases as type 2 diabetes mellitus (Soriano-Tarraga et al 2016), psoriasis (Zhou et al 2016), schizophrenia (Montano et al 2016), metabolic syndrome/obesity (Ali et al 2016) and many others have been recently published. It is expected that the new technologies that make possible this type of works and the technologies that will come allow epigenetic epidemiology to reach major objectives as the complete description of the epigenetic processes shaping the development of organisms, the interactions gene-epigene and epigene-environment, the establishment of the role of epigenetics in risk and emergence of diseases, as marker of disease or exposure, and the mechanisms of the inheritance of epigenetic changes over generations in humans (Bollati & Baccarelli 2010;Bakulski & Fallin 2014).…”
Section: Environmental Epigeneticssupporting
confidence: 67%
“…Similar studies with remarkable findings in the investigation of a variety of diseases as type 2 diabetes mellitus (Soriano-Tarraga et al 2016), psoriasis (Zhou et al 2016), schizophrenia (Montano et al 2016), metabolic syndrome/obesity (Ali et al 2016) and many others have been recently published. It is expected that the new technologies that make possible this type of works and the technologies that will come allow epigenetic epidemiology to reach major objectives as the complete description of the epigenetic processes shaping the development of organisms, the interactions gene-epigene and epigene-environment, the establishment of the role of epigenetics in risk and emergence of diseases, as marker of disease or exposure, and the mechanisms of the inheritance of epigenetic changes over generations in humans (Bollati & Baccarelli 2010;Bakulski & Fallin 2014).…”
Section: Environmental Epigeneticssupporting
confidence: 67%
“…This gene encodes a transcription factor that regulates TGF-β signaling and is mutated in nearly 90% of cases of ShprintzenGoldberg syndrome (OMIM #182212), a condition entailing craniofacial and brain anomalies [Au et al, 2014]. This gene is found to be methylated in SZ patients [Montano et al, 2016]. Indeed, in the brain, SKI regulates the proliferation and differentiation of neural precursors, along with the specification of cortical projections [Lyons et al, 1994;Baranek and Atanasoski, 2012].…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 99%
“…4 a) possibly indicative of an impaired glial function. Indeed, SKI methylation has been described in SZ brains [Montano et al, 2016].…”
Section: Functional Implication and Biological Interpretation Of Domementioning
confidence: 99%
“…Much of the work toward epigenetically characterizing the schizophrenia epigenome has involved measuring direct DNA methylation through bisulphite sequencing and similar methods. For example, a recent study (41 cases, 46 controls) across 4 brain regions found many genome regions that displayed differentially methylated DNA [28], while a larger study (689 cases, 645 controls) using blood samples similarly identified many differentially methylated loci [29]. Other studies support the importance of DNA cytosine methylation in schizophrenia [30-32].…”
Section: Mechanisms Of Epigenetic Regulationmentioning
confidence: 99%